Can a contemporary dietary assessment tool or wearable technology accurately assess the energy intake of professional young rugby league players? A doubly labelled water validation study - Costello, N.; Deighton, K.; Dalton-Barron, N.; Whitehead, S.; Preston, T.; Jones, B. (European Journal of Sport Science, 2019)
Accurate quantification of energy intake is imperative in athletes; however traditional dietary assessment tools are frequently inaccurate. Therefore, this study investigated the validity of a contemporary dietary assessment tool or wearable technology to determine the total energy intake (TEI) of professional young athletes.